Representasi Infrastruktur Data Desa Presisi di Desa Neglasari, Kabupaten Bogor - Badar Muhammad; Rajib Gandi; Sofyan Sjaf; Grace Natalie; Aushafa Dyazra (Jurnal Pusat Inovasi Masyarakat (PIM), 2021)
Development is a national agenda that is a priority of the nation. Sjaf et al. (2020) said that village development still has polemics about data accuracy. Positioning villagers as data objects is one of the reasons why village data presented by the auspices of the institution is not in accordance with the airy conditions. In addition, Sjaf (2019) also explained that the approach that has been done is not appropriate, thus causing data problems. Precision Village Data through the DPM approach seeks to initiate the construction of accurate data-driven villages. Involving the participation of villagers in the process of data retrieval and analysis is the purpose of making villagers as data subjects. IPB campus as a state university whose existence is surrounded by villages / villages, it is necessary to identify the forms of development programs and appropriate community service with data-based Precision Village. The database owned by Presisi Village Data can be used by the village as the foundation of neglasari village infrastructure development to increase the productivity of the village community. Data showing high internet usage in Neglasari Village is also a potential for science and technology development through education channels and infrastructure-related capacity development. Keywords: database, infrastructure, precision